If 5+3+2 = 151012, 9+2+4 = 183662, 8+6+3 = 482466 and 5+4+5 = 202504 then 7+2+5 = 143542. This sum is rather difficult to work out, but when the same rules are applied for the four solved sums in the question, it makes sense and is easier to comprehend. Take the first sum in the question to begin with: Multiply the first digit by the second digit (5 x 5 = 15). This provides us with the first two digits of the solution. Next multiply the first digit by the third digit (5 x 2 = 10); this provides the next two digits of the solution. Add the first and last digits together (5 + 2 = 7), and multiply the answer by the middle digit (7 x 3 = 21). Reverse the figure to achieve the final two digits, so 21 becomes 12. The answer to the first sum is, as stated, 151012. When you follow the same sequence of formulae through the second, third and fourth sums you will see that the answers are correct for each one. For example, to solve the the third sum: Multiply 8 (first digit) by 6 (second digit) to arrive at 48. Multiply the first digit by the last digit (8 x 3 = 24). Add the first (8) and last (3) digits together to get 11. Multiply 11 by 6 (second digit) to get 66. 66 reversed is 66 so the answer is 482466. So the answer to the final sum is achieved by multiplying 7 (first digit) and 2 (second digit) to arrive at 14, multiplying 7 (first digit) and 5 (last digit) to get 35. Add the first (7) and the last (5) digits together. The answer to this is 12. Multiply the 12 by the second digit (2) to arrive at 24. Reverse the 24 to 42 and the answer is 143542.

# Only 2% students had solve this CAT que in exam... 5+3+2=151012 9+2+4=183662 8+6+3=482466 5+4+5=202504 then 7+2+5?

7+2+5 = 143547

7*2=14

7*5=35

14(ans 1)+35(ans 2)=49(ans 3)

49(ans 3)-2(middle digit)=47

Finally

7+2+5 = 143547

7*2=14

7*5=35

14(ans 1)+35(ans 2)=49(ans 3)

49(ans 3)-2(middle digit)=47

Finally

7+2+5 = 143547

143542

It is not surprising. The meaning of the symbols in the expression is completely unconventional (therefore meaningless). Solution requires quite an agility of the imagination.

For those who have seen this before, the solution is simple.

A + b + c = (a*b)(a*c)(reversed digits of (b*(a+c)))

Filling in a=7, b=2, c=5, we get

7 + 2 + 5 = (7*2)(7*5)(2*(7+5)reversed) = 143542

For those who have seen this before, the solution is simple.

A + b + c = (a*b)(a*c)(reversed digits of (b*(a+c)))

Filling in a=7, b=2, c=5, we get

7 + 2 + 5 = (7*2)(7*5)(2*(7+5)reversed) = 143542

The answer is 7+2+5=143542.

143542

1)7×2=14

2)7×5=35

3)7+5=12

4)12×2=24

reverse of 24 it will be 42

so the ans ==143542

1)7×2=14

2)7×5=35

3)7+5=12

4)12×2=24

reverse of 24 it will be 42

so the ans ==143542

5+3+2=10, 9+2+4=15, 8+6+3=17, 5+4+5=14 and 7+2+5=14 therefore Ans. Is 5+4+5=14=202505